Obstetric anaesthesia. What is new? Geburtshilfliche analgesie und anästhesie. Gibt es neuigkeiten? - Reutershan, J.; Unertl, K. (gynäkologische praxis, 2010)
Obstetric anaesthesia is not only a challenging but also one of the most satisfying area of modern anaesthesiology. Challenges include the treatment of two »patients« at a time or rapid changes from an uncomplicated labour to a life-threatening emergency and demands substantial experience and knowledge from the anaesthesist in charge. Maternal mortality has constantly decreased over the past decade. Modern anaesthesiological concepts have considerably contributed to this development. However, there is still room for improvements. Many pregnant women still have reservations about epidural anaesthesia. Myths about complications, contraindications, or the ideal time to initiate an epidural are - even among experts - still controversial discussed. The difficult airway is still one of the most threatening events that is associated with high maternal mortality. This review highlights current concepts, recent advances, and future perspective in obstetric anaesthesia considering actual guidelines.
CRIS-Team Scopus Importer:2022-11-17
Keywords: Caesarian section; Epidural anaesthesia; Obstetric anaesthesia; Spinal anaesthesia